Developing Nature Tourism to Support Sustainable Development in Widosari Tourist Village - Lenny Kurnia Octaviani (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The potential of natural tourism in Indonesia is enormous and must be managed wisely. Tourism must be able to grow alongside sustainable development, taking into account economic, social, and environmental aspects. Many efforts have been made to combine tourism with the concept of the ecotourism, where tourism can thrive without damaging the environment, creating a sustainable tourism model. The research uses qualitative methodology to describe local phenomena and uses a single holistic model. This research aims to understand how natural tourism can develop in ways that support sustainable development, integrating economic, social, and environmental aspects. The study highlights examples of Widosari Tourism Village, where natural resources and unique social structures are used as tourist attractions. The results of the study show that Widosary Tourist Village has succeeded in developing natural tourism that not only attracts tourists but also supports sustainable development by paying attention to economic, social, and environmental aspects.